Cost Leadership Strategy and Performance of Media Houses in Kenya - Chief, Lyn Kwamboka; Mukulu, Elegwa; Karanja, Kabare (International Journal of Strategic Management, 2025)
Purpose: The aim of the study was to establish the effect of the cost leadership strategy on the performance of the media houses in Kenya. The objectives were to determine the relationship between the cost leadership strategy and the performance of media houses and to establish the moderating role of technology on the relationship between cost leadership strategy and performance of the media houses in Kenya. Methodology: The study adopted survey research design. The target population was the 41 media houses in Kenya. The study targeted the top management of the media houses which comprised of the Finance, Marketing, Operations and information Communication Departments. According to the human resource of the organizations, there are about 1,976 management staff in the media houses in Kenya. 204 respondents were sampled purposive, stratified and simple random sampling. Data was collected using structured questionnaires and interview guides. Data was analysed using both descriptive and inferential statistics which included regression and moderation analysis. The researcher also tested the hypothesis. The results were presented in tables. Findings: The study established that media firms employed cost leadership to a moderate extent. The study established that most of the media firms used low cost of production with particular focus on the cost of production and advertising rates. The firms also relied on use of technology to enhance their efficiency and thus minimize the cost of production thus driving down costs. The firms emphasized the use of economies of scale where possible to minimize the costs of production, thus keeping their prices down. Firms minimized wastages by ensuring capacity utilization of resources. The introduction of technology as moderators had no significant effect on the cost leadership strategy. The introduction of technology in the cost leadership model resulted to increase in the R-squared meaning that technology adoption enhanced the relationship between cost leadership and media firm performance. Unique Contribution to Theory, Practice and Policy: The study recommended that media firms utilize cost leadership strategy by emphasizing minimization of operating costs such as and adopting cost saving measures such as outsourcing, economies of scale, capacity utilization of resources to help achieve competitiveness and improve performance.